New Straits Times, 15 July 2008 - Shanti Gunaratnam (The New Straits Times Press (M) Bhd, 2008)
His English is impeccable as is his Bahasa Malaysia, son of Haji Abdul Ghani, is the primary caretaker of Villa Sentosa.